Examining the neuroanatomical and the behavioural basis of the effect of basic rhythm on reading aloud. Issue 6 (3rd July 2017) - Gould, Layla; Mickleborough, Marla J. S.; Ekstrand, Chelsea; Lorentz, Eric; Borowsky, Ron
ABSTRACT: We used functional magnetic resonance imaging (fMRI) to examine the brain regions associated with the effect of congruency between rhythmic stress and syllabic stress on reading aloud (Gould et al., 2016). The region of particular interest was the putamen, which has been shown to be involved in speech processing, rhythm processing, and predicting upcoming events. The task involved naming words that placed the stress on either the first or second syllable (practice versus police), as well as their corresponding pseudohomophones (praktis versus poleese) that were preceded by either a congruent or incongruent rhythmic prime. The fMRI results revealed that a network involving the putamen is involved, and the behavioural results demonstrated that a rhythmic prime matched to the syllabic stress aids reading processes of both words and PHs. Implications for neurobiological models of reading, as well as clinical applications (e.g. speech rehabilitation in Parkinson's disease) are discussed.